At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the equation of [tex]\( g(x) \)[/tex] based on the given function [tex]\( f(x) = (x - 3)^2 \)[/tex] and the information about the vertical stretch, we will follow these steps:
1. Identify the given function: [tex]\( f(x) = (x - 3)^2 \)[/tex]
2. Vertical stretch factor: The stretch factor is given as 2. This means the output of the function [tex]\( f(x) \)[/tex] will be multiplied by 2 to give the new function [tex]\( g(x) \)[/tex].
3. Apply the vertical stretch to the function: To incorporate the vertical stretch factor into [tex]\( f(x) \)[/tex], we multiply the entire function by the stretch factor.
So, [tex]\( g(x) = 2 \cdot f(x) \)[/tex].
4. Substitute [tex]\( f(x) \)[/tex] into the equation: Replace [tex]\( f(x) \)[/tex] with [tex]\((x - 3)^2\)[/tex].
Therefore, [tex]\( g(x) = 2 \cdot (x - 3)^2 \)[/tex].
So, the equation of [tex]\( g(x) \)[/tex] is:
[tex]\[ g(x) = 2(x - 3)^2 \][/tex]
To confirm, let's evaluate [tex]\( g(x) \)[/tex] at some specific points, ensuring our transformation is correct:
- For [tex]\( x = 0 \)[/tex]:
[tex]\( g(0) = 2(0 - 3)^2 = 2 \cdot 9 = 18 \)[/tex]
- For [tex]\( x = 1 \)[/tex]:
[tex]\( g(1) = 2(1 - 3)^2 = 2 \cdot 4 = 8 \)[/tex]
- For [tex]\( x = 2 \)[/tex]:
[tex]\( g(2) = 2(2 - 3)^2 = 2 \cdot 1 = 2 \)[/tex]
These evaluations confirm that our derived equation [tex]\( g(x) = 2(x - 3)^2 \)[/tex] gives the correct function values as expected.
1. Identify the given function: [tex]\( f(x) = (x - 3)^2 \)[/tex]
2. Vertical stretch factor: The stretch factor is given as 2. This means the output of the function [tex]\( f(x) \)[/tex] will be multiplied by 2 to give the new function [tex]\( g(x) \)[/tex].
3. Apply the vertical stretch to the function: To incorporate the vertical stretch factor into [tex]\( f(x) \)[/tex], we multiply the entire function by the stretch factor.
So, [tex]\( g(x) = 2 \cdot f(x) \)[/tex].
4. Substitute [tex]\( f(x) \)[/tex] into the equation: Replace [tex]\( f(x) \)[/tex] with [tex]\((x - 3)^2\)[/tex].
Therefore, [tex]\( g(x) = 2 \cdot (x - 3)^2 \)[/tex].
So, the equation of [tex]\( g(x) \)[/tex] is:
[tex]\[ g(x) = 2(x - 3)^2 \][/tex]
To confirm, let's evaluate [tex]\( g(x) \)[/tex] at some specific points, ensuring our transformation is correct:
- For [tex]\( x = 0 \)[/tex]:
[tex]\( g(0) = 2(0 - 3)^2 = 2 \cdot 9 = 18 \)[/tex]
- For [tex]\( x = 1 \)[/tex]:
[tex]\( g(1) = 2(1 - 3)^2 = 2 \cdot 4 = 8 \)[/tex]
- For [tex]\( x = 2 \)[/tex]:
[tex]\( g(2) = 2(2 - 3)^2 = 2 \cdot 1 = 2 \)[/tex]
These evaluations confirm that our derived equation [tex]\( g(x) = 2(x - 3)^2 \)[/tex] gives the correct function values as expected.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.